Effects of the TPACK Levels of University Teachers on the Use of Online Teaching Technical Tools - Tao, YaPing; Ma, JianHua (International Journal of Emerging Technologies in Learning (iJET), 2022)
Abstract—The effects of technological pedagogical content knowledge (TPACK) on teachers’ use of online teaching technical tools are analyzed through a case study based on 297 civil engineering teachers in 7 universities of China. Results show that the overall Cronbach’s α is 0.868, Kaiser–Meyer–Olkin test (KMO)is 0.781, and the corresponding P value is 0.000, indicating the high reliability and validity of the study. The content knowledge(CK), technological knowledge(TK), and TPACK of civil engineering teachers in universities have significantly positive effects on their use of online teaching technical tools. Conclusions can provide important references to expand the research scope and content of TPACK, promote the professional development of civil engineering teachers in universities, and help them enrich information knowledge structure.